Investigating grouting body nonuniform expansion in anisotropic underground soil mechanics - Bosong Ding; Ping Lou; Can Huang; Weihang Li; You Wang (Scientific Reports)
Abstract An improved method tailored for anisotropic soft soils is presented, integrating theoretical models and field data to calculate the grouting quantity required for tunnel foundations. Given the complexities of soil interactions, particularly under variable geological conditions, this approach incorporates nonlinear behaviors and empirical field data to improve accuracy. Our findings reveal that integrating these theoretical frameworks significantly enhances the understanding of stress–strain behavior during grouting, enabling precise calculations of both axial and vertical expansion. Validation against numerical simulations demonstrates the model’s reliability, highlighting the influence of soil types and grouting depths on expansion dynamics. This method not only helps mitigate risks in tunnel construction but also enhances foundation reinforcement strategies, driving progress in geotechnical engineering. It is particularly valuable for urban tunnel projects in complex geological conditions, where ensuring ground stability and safety is crucial.